ADOLESCENT KNOWLEDGE ABOUT SEXUALITY AND REPRODUCTIVE HEALTH: VALIDITY AND RELIABILITY TESTS OF RESEARCH INSTRUMENTS AND ITS INTERPRETATION - Yulli Fety; Faridah Moh Said; Nisha Nambiar (Green Publisher, 2023)
Adolescents have sexual and reproductive health needs. Adolescence is a transitional period that needs to be given an understanding of sexual and reproductive health. One of the efforts that can be made so that adolescents get information about sexual and reproductive health is health education about sexuality. Talking about sexual and reproductive health is no longer taboo. This paper aims to identify content validity testing questions about adolescent knowledge related to sexual and reproductive health. This research was conducted in 4 schools in the city of Kendari which were divided into 2 groups (case and control). The two groups were jointly given a questionnaire (pre-posttest) on sexual and reproductive health. The sample in this study were boys and girls in class X-XI adolescents aged 15-17 years. This study uses a true experiment. The control group was not given intervention while the case group was given intervention. Data collection using a questionnaire. The pretest-posttest results in the control group showed an Asymp.Sig(2-tailed) value of 0.029, in the case group with an Asymp.Sig(2-tailed) value of 0.000. In this study to test the validity and reliability of the questionnaire instrument used was the Alpha Cronbach Test